2020
DOI: 10.48088/ejg.h.gek.11.2.47.64
|View full text |Cite
|
Sign up to set email alerts
|

Hidden geographies of population implosion in Bosnia and Herzegovina

Abstract: Bosnia and Herzegovina has witnessed continuous depopulation since 1991. Depopulation was foreseen even without the emergence of war, but not nearly to that extent or that early. Bosnia and Herzegovina is in a worse demographic position than the European Union countries that show similar demographic trends. Very low birth rates, low fertility and low natural population growth have been recorded in the time of weaker economic development, which increasingly accelerates the emigration of the educated population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Population ageing is influenced by a variety of factors, including demographic, economic, social, environmental, health, and health care (Wan et al, 2022;Beard & Bloom, 2015;Almedia de Melo et al, 2010). Various studies have shown that numerous variables contribute to population ageing disparities in different areas of Bosnia and Herzegovina, with social, economic, and political factors being the most significant (Gekic et al, 2020;Gekic et al, 2021;Kadusic, Suljic, 2018). These factors have had a considerable impact on the demographic patterns and processes of Bosnia and Herzegovina's population at the beginning of the 21st century.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population ageing is influenced by a variety of factors, including demographic, economic, social, environmental, health, and health care (Wan et al, 2022;Beard & Bloom, 2015;Almedia de Melo et al, 2010). Various studies have shown that numerous variables contribute to population ageing disparities in different areas of Bosnia and Herzegovina, with social, economic, and political factors being the most significant (Gekic et al, 2020;Gekic et al, 2021;Kadusic, Suljic, 2018). These factors have had a considerable impact on the demographic patterns and processes of Bosnia and Herzegovina's population at the beginning of the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies on Bosnia and Herzegovina's demographic trends have been conducted. For example, Gekic et al (2020) studied depopulation trends in Bosnia and Herzegovina at the end of the 20th and beginning of the 21st centuries, whereas Gekic et al (2019) researched spatial differentiation of the age structure of the population in Bosnia and Herzegovina. Mijic & Ateljevic (2018) studied the use of contemporary GIS software in demographic research of the Bosnian entity of the Republic of Srpska.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to unemployment, inadequacy of the education system, depressing political situation, and the lack of prospects for a better future have all contributed to the mass emigration of young people. Existential problems of the youth also have a strong impact on having fewer children than desired (Gekić et al 2020).…”
Section: Recent Demographic Trendsmentioning
confidence: 99%
“…It is clear that all sciences, including geography, are concerned in some way with the hidden, the undiscovered, the unknown (see Kumer 2020, Klun 2020, Gekic et al 2020, Orgin et al 2020, Kim & Muhič 2020, Planinc 2020. Moreover, interest in phenomena beyond the visible sphere (i.e., hidden) is in the core of geography, even though the name of the discipline itself, as well as its many definitions, imply a concern with the "surface of the earth," its physical features, material, and mappable objects and structures.…”
mentioning
confidence: 99%